The Effect of Adding High-Density Polyethylene Polymer on the Engineering Characteristics for Sandy Soil (Journal of Engineering, 2021)
The loose sand is subject to large settlement when it is exposed to high stresses. This settlement is due to the nature of the high drainage of sand, which displays foundations and constructions to a large danger. The densification of loose sandy soils is required to provide sufficient bearing capacity for the structures. Thus soil stabilization is used to avoid failure in the facilities. Traditional methods of stabilized sandy soil such as fly ash, bituminous, and cement often require an extended curing period. The use of polymers to stabilize sandy soils is more extensive nowadays because it does not require a long curing time in addition to being chemically stable. In this study, the effect of adding different percentages of high-density polyethylene HDPE  to the sandy soils' engineering characteristics such as the angle of internal frictions Ø0, shear strength τ, California Bearing Ratio CBR, and permeability k was studied. The results of laboratory tests showed that using of HDPE at percentages  (0.1, 0.3, 0.6, 1, and 3%) led to a decrease in soil permeability by 18% and an increase in both the angle of internal friction, the CBR value, and shear strength about 27.2%, 180.9%, and 38.6 % respectively by adding 1%. HDPE.